[Afisz. Incipit] Ogłoszenie. Na podstawie art. 20 ustawy ... o tymczasowym uregulowaniu finansów komunalnych ... / A. Bartoszewski. - Bartoszewski, Adam ([wydawca nieznany], 1946)
Afisz dotyczący podatku za psy z 8.01.1946 r.